IMPLEMENTASI DANA DESA MENURUT UNDANG-UNDANG NOMOR 6 TAHUN 2014 - Kasman Siburian; Hisar Siregar; Tri Dennis Boy Silitongan (LPPM Universitas HKBP Nommensen, 2020)
The presence of the Law on Villages, namely Law No.6 of 2014 strengthens the status of the Village as a community government as well as a Village power to build infrastructure and prosper the Village community. Villages receive transfer funds from the regions in the form of Village Fund Allocation (ADD). This research was conducted in Lobusiregar II Village, Siborongborong District, North Tapanuli Regency. This study aims to analyze village financial management in managing the Village Fund Allocation. This type of research is a juridical emipirical legal research with a descriptive analysis approach. This research was conducted using documentation techniques and interviews with parties involved in ADD management. The results of the description are obtained through the analysis of Permendagri No. 113 of 2014 by comparing the realization in the field.